Generative imitation, strategic distancing and optimal distinctiveness during the growth, decline and stabilization of Silicon Alley - Garud, Raghu; Lant, Theresa K.; Schildt, Henri A. (Innovation (North Sydney), 2019)
We embrace a cultural perspective on entrepreneurship to examine the performative relationship between entrepreneurial narratives and the field discourse that unfolded during the emergence of the 'new media' field in New York city that came to be known as 'Silicon Alley'. During growth, the accumulation of projective entrepreneurial narratives generated a field discourse from which entrepreneurs drew. However, because of the hype generated and the implementation challenges encountered by the ventures, the expectations set by the entrepreneurs remained unrealized, thereby leading to failures. The loss of legitimacy that accrued to these ventures spread to others through the cultural symbols shared by the ventures, which led to the collapse of the field. Opportunities based on cultural symbols considered valuable during early stages now became worthless. The Silicon Alley field eventually stabilized as entrepreneurs offered revised narratives to generate renewed growth. Based on these dynamics, we introduce generative imitation and strategic distancing as narrative-discursive possibilities to complement the notion of optimal distinctiveness. We propose that optimal distinctiveness best describes narrative-discursive possibilities and efforts when fields have stabilized, whereas generative imitation and strategic distancing better describe possibilities and efforts during growth and decline periods respectively.